2015
DOI: 10.1007/s00244-015-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pesticide Exposure in a Sample of Pregnant Women in Ecuador

Abstract: Background Few studies have detailed the prenatal pesticide exposure levels of women employed in or residing near large-scale agricultural industries. This study reports pesticide metabolite levels during and shortly after pregnancy in a pilot study of workers in Ecuador. Methods Urine samples were collected for 16 rose workers and 10 non-agricultural workers enrolled into the study in early pregnancy. We measured six nonspecific organophosphate dialkylphosphate (DAP) pesticide metabolites, two alkylenebis-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 55 publications
0
9
1
1
Order By: Relevance
“…To the best of our knowledge, no other study has evaluated the urine concentrations of pyrethroid metabolites in a migrant Mexican population. In comparison to studies outside of Sonora, urinary concentrations of 3PBA were higher than the results obtained from the North Carolina studies by Raymer et al [41] and Arcury et al [38] as well as those reported by Panawet et al [38] in Thailand and a study conducted by Handal et al [40] in Ecuador with rose-workers (Table 5). Meanwhile, urinary concentrations for 4F3PBA and t-DCCA in our exploratory study were higher than the results reported by Handal et al [40] in Ecuador, but they were not reported in the other farmworker studies [38,39,41] (Table 5).…”
Section: Discussioncontrasting
confidence: 57%
“…To the best of our knowledge, no other study has evaluated the urine concentrations of pyrethroid metabolites in a migrant Mexican population. In comparison to studies outside of Sonora, urinary concentrations of 3PBA were higher than the results obtained from the North Carolina studies by Raymer et al [41] and Arcury et al [38] as well as those reported by Panawet et al [38] in Thailand and a study conducted by Handal et al [40] in Ecuador with rose-workers (Table 5). Meanwhile, urinary concentrations for 4F3PBA and t-DCCA in our exploratory study were higher than the results reported by Handal et al [40] in Ecuador, but they were not reported in the other farmworker studies [38,39,41] (Table 5).…”
Section: Discussioncontrasting
confidence: 57%
“…Urinary metabolites of OPPs, i.e., DAPs, have short half-lives ranging from 2 to 15.5 h [ 17 , 18 ]. One study on Japanese pregnant women reported intra-class correlation coefficients (ICCs) to be 0.42–0.55 [ 21 ], while studies conducted in other countries provided −0.01–0.52 [ 51 , 56 , 57 , 58 ]. According to the rule of thumb, an ICC of 0.4 is categorised as “moderate” [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“… 36 Another study reported elevated thiourea levels in pregnant agricultural rose workers in Ecuador. 37 …”
Section: Discussionmentioning
confidence: 99%